Thermal decomposition of crystalline Ni-II-Cr-III layered double hydroxide: A structural study of the segregation process - Sileo, E. E.; Jobbagy, M.; Paiva-Santos, C. O.; Regazzoni, A. E. (Amer Chemical Soc, 2005)
A structural study of the thermal evolution of Ni0.69Cr0.31(OH)(2)(CO3)(0.155)(.)nH(2)O into NiO and tetragonal NiCr2O4 is reported. The characteristic structural parameters of the two coexisting crystalline phases, as well as their relative abundance, were determined by Rietveld refinement of powder x-ray diffraction (PXRD) patterns. The results of the simulations allowed us to elucidate the mechanism of the demixing process of the oxides. It is demonstrated that nucleation of a metastable nickel chromite within the common oxygen framework of the parent Cr-III-doped bunsenite is the initial step of the cationic redistribution. The role that trivalent cations play in the segregation of crystalline spinels is also discussed.